Preparation and characterization of halogen-free flame retardant MCA core-shell microcapsules coated with melamine or acrylic acid resin - Zhang, Xiaoyi; Gu, Zheng; Sui, Jinyong; Zhenxu Li, Zhenxu Li; Song, Lining; Yang, Lina; Wang, Ning; Zhao, Jie (Polimery, 2021)
The resin melamine cyanurate (MCA) core-shell microcapsules were prepared by surface coating modification of halogen-free flame retardant MCA using melamine resin and acrylic resin as wall materials. The influence of different wall materials on the coating effect of halogen-free flame retardant MCA was studied by SEM, particle size analysis, IR, and DSC and TGA methods. The results showed that the melamine resin had a high degree of polymerization and decomposed at about 160°, which had a surface modification effect on MCA and did not affect its flame retardant performance. The surface coating rate of poly(methyl methacrylate) PMMA-MCA core-shell microcapsules was about 80%. After adding acrylic acid (AA) as the second monomer the coating effect was significantly improved and the thermal decomposition temperature of the wall material of the microcapsule was reduced.